2019
DOI: 10.1002/mame.201900244
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Designable Textile Pattern Strain Sensors Based on Graphene Decorated Conductive Nylon Filaments

Abstract: Flexible sensors with stretchable and wearable characteristics have boosted wide interest in human motion detection and physiological signal monitoring. However, the majority of current sensors suffer from the lack of seamlessly integrated with clothes substrates, hindering their applications as “real” wearable devices. Herein, a facile low‐cost and scalable continuous capillary dip coating route is employed to deposit graphene inks onto nylon filaments to obtain graphene decorated nylon conductive filaments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Nevertheless, the method of combining graphene-based materials with yarns through dip-coating [ 58 , 59 , 65 , 66 , 67 , 68 , 70 ], layer-by-layer (LbL) assembly [ 60 , 61 , 62 , 63 ] is more widely used. Hamid Souri et al [ 58 ] coat natural fiber yarns with graphene nanoplatelets (GNPs) and carbon black (CB) to obtain conductive yarns.…”
Section: Preparation Methods and Performance Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the method of combining graphene-based materials with yarns through dip-coating [ 58 , 59 , 65 , 66 , 67 , 68 , 70 ], layer-by-layer (LbL) assembly [ 60 , 61 , 62 , 63 ] is more widely used. Hamid Souri et al [ 58 ] coat natural fiber yarns with graphene nanoplatelets (GNPs) and carbon black (CB) to obtain conductive yarns.…”
Section: Preparation Methods and Performance Evaluationmentioning
confidence: 99%
“…The performance of various graphene-based staple and filament yarn strain sensors are summarized in Table 2 . It can be found that the GF absolute value of staple and filament yarn strain sensors present different variation trends with the increase of strain [ 59 , 65 , 66 , 68 , 70 ]. In the process of stretching, yarn deformation can be divided into two processes.…”
Section: Preparation Methods and Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to achieve a conductive polyamide, several methods have been adopted in recent years, which can be classified into two types according to the categories of antistatic agents. First, conductive nanoparticles [ 8 , 9 ], including carbon nanotubes [ 10 , 11 , 12 , 13 ], graphene [ 14 , 15 , 16 , 17 , 18 ] and carbon black [ 19 , 20 , 21 , 22 ], have been popular for use in fabricating polyamide-based nanocomposites. Here, enhancing the interfacial adhesion between nanopowders and the corresponding matrix has attracted a great deal of attention as it determines the ultimate properties of the composites.…”
Section: Introductionmentioning
confidence: 99%